2012
DOI: 10.1088/1742-6596/359/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Study of Barley Grain Molecular Structure for Ruminants Using DRIFT, FTIR-ATR and Synchrotron Radiation Infrared Microspectroscopy (SR-IMS): A Review

Abstract: Abstract. Barley inherent structures are highly associated with nutrient utilization and availability in both humans and animals. Barley has different degradation kinetics compared with other cereal grains. It has a relatively higher degradation rate and extent, which often cause digestive disorder in the rumen. Therefore understanding barley inherent structure at cellular and molecular levels and processing-induced structure changes is important, because we can manipulate barley inherent structures and digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…31 For most bacteria in the rumen, ammonia is their primary nitrogen source. 32 Therefore, introduction of N 15 labeled ammonia sulfate would be helpful in tracing microbial synthesis during the fermentation. The higher APE of LAMN than LMN was consistent with a previous study, 20 implying higher N assimilation in particle-attached microbes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 For most bacteria in the rumen, ammonia is their primary nitrogen source. 32 Therefore, introduction of N 15 labeled ammonia sulfate would be helpful in tracing microbial synthesis during the fermentation. The higher APE of LAMN than LMN was consistent with a previous study, 20 implying higher N assimilation in particle-attached microbes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, transgenic alfalfa also showed alterations in molecular structure with attenuated total reflectance–Fourier transform infrared (ATR-FTIR) spectroscopy . FTIR spectroscopy is a rapid analytical tool to reveal the inherent molecular structures of samples and has been applied to feed ingredients recently. Molecular structures are closely related to nutrient content and availability and could be used to predict nutrient profiles of samples. ,, The current study aimed to evaluate the effects of silencing HB12 and TT8 in alfalfa on protein degradation and intestinal digestion, microbial protein synthesis, and protein metabolic profiles. In addition, correlations and regressions between these nutritional profiles and FTIR spectral parameters were also determined.…”
Section: Introductionmentioning
confidence: 99%
“…The true nutritive values of feeds are associated with both chemical composition and internal molecular structure, because the nutrient bioavailability and fermentation features are influenced by internal structure. , However, the inherent structures of feed samples are usually destroyed during the conventional “wet chemical analysis” methods (e.g., AOAC , ), and the wet chemical analysis fails to link chemical composition to inherent structure. , …”
Section: Introductionmentioning
confidence: 99%
“…With six components (electron gun, linear accelerator, booster ring, storage ring, beamlines, and experimental stations), the synchrotron could turn electrons into extreme bright light and then show inherent structure of biological tissues . This synchrotron-based technique is capable of showing four kinds of tissue information (tissue structure, tissue chemistry, tissue environment, and tissue composition) within different layers at the same time. ,, Several studies have been done with the successful application of this synchrotron technique to reveal molecular structure and structure changes by different treatments of various feedstuff in our laboratories. ,,, With the development and application of this technique, the relationship between molecular structure and biological functions could be explained from the revealed differences in spectra from SR-IMS according to the previous research. However, to date, few studies have been found on molecular structure in relation to biofunctions and bioavailability of nutrients in carinata seeds and carinata meal except our preliminary study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation